2022
DOI: 10.3390/agriculture12111825
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and Calibration of DEM Parameters of Soybean Seed Particles

Abstract: In discrete element method (DEM) simulations, accurate simulation parameters are very important. For ellipsoidal soybean seed particles, the rolling friction coefficient between seed particles (RFCP-P) and the rolling friction coefficients between seed particle and boundary (RFCP-B) are difficult to measure experimentally and therefore need to be calibrated. In this paper, soybean seed particles of three varieties with different sphericities were taken as the research objects. Through the simulation analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Due to the high sphericity of soybean seeds [18] and their good rollability and mobility, a shaftless spiral seed discharging and delivery device was designed based on the principle of spiral conveying. Using its rotational pushing principle and the flexibility of the shaftless spiral, the seed discharging and the restrained seed guiding of soybean seeds were realized, and the structure schematic is shown in Figure 3.…”
Section: Design Of Key Components 221 Structure and Parameter Design ...mentioning
confidence: 99%
“…Due to the high sphericity of soybean seeds [18] and their good rollability and mobility, a shaftless spiral seed discharging and delivery device was designed based on the principle of spiral conveying. Using its rotational pushing principle and the flexibility of the shaftless spiral, the seed discharging and the restrained seed guiding of soybean seeds were realized, and the structure schematic is shown in Figure 3.…”
Section: Design Of Key Components 221 Structure and Parameter Design ...mentioning
confidence: 99%
“…Currently, the soybean particle model derived from MS has been applied in numerous studies on the calibration of soybean contact parameters [17][18][19][20][21][22][23]. Despite the results of the proceeding investigations are incompatible with the contact properties of the soybeanbonded particle model, the calibration process and experimental setup are highly bene cial and instructive for this study.…”
Section: Introductionmentioning
confidence: 99%
“…Zhou H. et al, (2022), determined the DEM parameters of paddy soil with high moisture content (>40%) by using the Hertz-Mindlin with JKR model. Yan D. et al, (2022), measured and calibrated the RFCP-P and RFCP-B of soybean seed particles of three varieties with different sphericity. The above studies have calibrated the key DEM parameters of the particles, which improved the accuracy of related simulation studies, but there is no related study reported on green onion seeds and similar seeds.…”
Section: Introductionmentioning
confidence: 99%